ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA SEBELUM DAN SAAT PANDEMI COVID-19 PADA PT ZONA PROPERTY - Istiarsih, Fitri; Nursidin, M.; Risuhendi, Risuhendi (UNIVERSITAS DHARMAWANGSA, 2024)
Companies in the property or real estate sector are starting to experience the impact of the slowdown due to the onset of the Covid-19 outbreak. In this case, it is necessary to have an assessment of financial performance by analyzing the company's financial statements in a given period. Generally, the ratio that is often used to measure the performance of a company is the liquidity ratio, the solvency ratio and the profitability ratio. The problem formula in this study is how the financial condition if measured from the liquidity ratio covers the current ratio and the cash ratio? How does the financial condition if measured from the solvency ratio include the debt to equity ratio and the Debt to asset ratio? How do financial conditions be measured from the profitability ratio to include the gross profit margin and the net profit margin? And the purpose of this research is to find out and analyze the financial performance of the Property Zone if measured by the liquidity ratio (current ratio and cash ratio), to know and analyse the financial performances of the property zone if measurable by the solvency ratio, and to learn and analyse financial performance at the Properties Zone when measuring by the profitability ratio. (gross profit margin dan net profit margin). The results of this study showed that the liquidity ratio and solvency ratio of PT Zone Property was rated very well because the total average ratio was in accordance with industry average standards.